Evaluation of cowpea genotypes for their reactions to Striga gesnerioides in the dry savanna of northeast Nigeria - Omoigui, L.O.; Kamara, A.Y.; Massawe, F.S.; Ishiyaku, M.F.; Boukar, O.; Alabi, S.O.; Ekeleme, F. (African Crop Science Society, 2007)
The parasitic weed Striga gesnerioides (Willd) Vatke is one of the most important constraints to cowpea production in the dry savanna. Yield losses due to S. gesnerioides range from 83 to 100%. No single method however seems to be fully adequate in the control of this parasite. One practice, host plant resistance, appears to have merit in effectively and economically controlling the parasite in that it is affordable to farmers. A total of 30 breeding lines including some varieties were evaluated in a field trial at Damboa and Tilla in 2005 and 2006 to identify resistant parents that could be used in breeding programme. Results showed varietal difference with respect to Striga infection in the genotypes studied. Location and cultivars were found to be associated with yield losses in soils infested by Striga. The location effect was probably due to lower soil fertility and severity of Striga damage. Cultivars effect was evident at both locations. The cowpea varieties B301, IT00K-1217, IT97K-205-8, IT03K-338-1 and IT97K-499-35 showed complete resistance to Striga while cowpea varieties IT81D-994, 1T98K-503-1, IT99K-7-21-2-2 and IT98K-216-44 earlier reported to be resistant supported many emerged Striga shoot, thus, suggesting the presence of different strains of Striga in the region. On the other hand, the varieties like Borno local, IT84S-2246-4, IT98D-1399, TVU-7778 and TVX-3236 have low yield potential as well as susceptible to Striga. Average yield loss in susceptible variety (Borno local) relative to the mean yield of resistant cultivars was 44%. There was a strong negative correlation (r = - 0.537) between grain yield and emerged Striga shoot. A significant negative (r = - 0.391, r = - 0.188) correlation was also obtained between grain yield, pods per plant and Striga height. This information showed that there is sufficient genetic variability in the cowpea genotypes studied, which can be exploited in breeding cowpea varieties for resistance to S. gesnerioides. A great progress toward developing improved cowpea germplasm that has local phenotypes with durable resistance to S. gesnerioides can be achieved if the genes from the resistance cultivars identified could be introgressed into the adapted susceptible local varieties in the area. This will further increase the potential impact of adoption of resistant cowpea varieties in the zone.